Neuronal migration is retarded in mice lacking the tissue plasminogen activator gene - Seeds, Nicholas W. (National Academy of Sciences, 1999)
Neuronal migration is a critical phase of brain development, where defects can lead to severe ataxia, mental retardation, and seizures. In the developing cerebellum, granule neurons turn on the gene for tissue plasminogen activator (tPA) as they begin their migration into the cerebellar molecular layer. Granule neurons both secrete tPA, an extracellular serine protease that converts the proenzyme plasminogen into the active protease plasmin, and bind tPA to their cell surface. In the nervous system, tPA activity is correlated with neurite outgrowth, neuronal migration, learning, and excitotoxic death. Here we show that compared with their normal counterparts, mice lacking the tPA gene (tPA(−/−)) have greater than 2-fold more migrating granule neurons in the cerebellar molecular layer during the most active phase of granule cell migration. A real-time analysis of granule cell migration in cerebellar slices of tPA(−/−) mice shows that granule neurons are migrating 51% as fast as granule neurons in slices from wild-type mice. These findings establish a direct role for tPA in facilitating neuronal migration, and they raise the possibility that late arriving neurons may have altered synaptic interactions.